2016
DOI: 10.1080/00036846.2016.1226491
|View full text |Cite
|
Sign up to set email alerts
|

Stock prices, inflation and inflation uncertainty in the U.S.: testing the long-run relationship considering Dow Jones sector indexes

Abstract: We test for the long-run relationship between stock prices, inflation and its uncertainty for different U.S. sector stock indexes, over the period 2002M7 to 2015M10. For this purpose we use a cointegration analysis with one structural break to capture the crisis effect, and we assess the inflation uncertainty based on a time-varying unobserved component model. In line with recent empirical studies we discover that in the long-run, the inflation and its uncertainty negatively impact the stock prices, opposed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…In the short-term dynamics of the relationship, inflation has a negative but insignificant effect on the return of the Islamic stock index in Indonesia in the lag of the previous quarter and two lags of the previous quarter. Albulescu et al (2017) say that macroeconomic fundamentals only guide long-term institutional investors, whereas short-term traders are guided by the current economic context and by the uncertainties that characterize it. Changes in inflation are not a factor that investors pay attention to in the observation period of this study, Islamic stock investors believe that in those years the economic conditions began to stabilize after the 1997 and 2008 economic crises, so investors invested by looking at o ther macroeconomic indicators.…”
Section: A) Indonesiamentioning
confidence: 99%
“…In the short-term dynamics of the relationship, inflation has a negative but insignificant effect on the return of the Islamic stock index in Indonesia in the lag of the previous quarter and two lags of the previous quarter. Albulescu et al (2017) say that macroeconomic fundamentals only guide long-term institutional investors, whereas short-term traders are guided by the current economic context and by the uncertainties that characterize it. Changes in inflation are not a factor that investors pay attention to in the observation period of this study, Islamic stock investors believe that in those years the economic conditions began to stabilize after the 1997 and 2008 economic crises, so investors invested by looking at o ther macroeconomic indicators.…”
Section: A) Indonesiamentioning
confidence: 99%
“…The changes in crude oil prices affect the Inflation; Mork's (1989) determined the affects of oil prices on inflation rate and stock returns. Albulescu et al (2016), Cunado and Perez de Gracia (2005), Fletcher (2000) showed that oil prices, stock exchange and inflation rate have significant positive relation with each other. Many studies showed that there is a positive affect of crude oil prices on inflation rate, CPI, stock market, and gold prices.…”
Section: Impact Of Oil Prices On Inflation and Stock Returnsmentioning
confidence: 92%
“…According to the studies, if inflation rate escalated then simultaneously equity prices also rise, so, this phenomenon concluded a direct relationship (Wulfsberg 2016). However, some studies examined negative association between inflation rate and stock returns (e.g., Ratti, Vespignani 2016;Haugom et al 2016;Jiang, Gu 2016;Albulescu et al 2016;Mushtaq 2012;etc.). Numerous studies investigated the affects of interest and inflation rates on equity returns, and concluded that inflation and interest rate have an inverse association on stock returns (e.g., Gomes 2015;Sultonov 2015;Gilmore et al 2015;etc.…”
Section: Impact Of Oil Prices On Inflation and Stock Returnsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their research found connection inflation and stock is more positive for the pro-cyclical stock than noncyclical stock after the 1980s; it possesses no hedging properties. After 2008 two factors occurred: (1) stock had started to portray hedging abilities in various economies (Spierdijk et al, 2015;Cifter, 2015), and (2) a decline in the number of firms that hedge against inflation (Bampinas et al, 2016). These factors affect firms' risk management abilities, especially in small open economies such as the Croatian economy.…”
Section: Introductionmentioning
confidence: 99%